N-Arylphenothiazines as strong donors for photoredox catalysis – pushing the frontiers of nucleophilic addition of alcohols to alkenes - Speck, Fabienne; Rombach, David; Wagenknecht, Hans-Achim (Beilstein Journal of Organic Chemistry, 2019)
A new range of N-phenylphenothiazine derivatives was synthesized as potential photoredox catalysts to broaden the substrate scope for the nucleophilic addition of methanol to styrenes through photoredox catalysis. These N-phenylphenothiazines differ by their electron-donating and electron-withdrawing substituents at the phenyl group, covering both, σ and π-type groups, in order to modulate their absorbance and electrochemical characteristics. Among the synthesized compounds, alkylaminylated N-phenylphenothiazines were identified to be highly suitable for photoredox catalysis. The dialkylamino substituents of these N-phenylphenothiazines shift the estimated excited state reduction potential up to −3.0 V (vs SCE). These highly reducing properties allow the addition of methanol to α-methylstyrene as less-activated substrate for this type of reaction. Without the help of an additive, the reaction conditions were optimized to achieve a quantitative yield for the Markovnivkov-type addition product after 20 h of irradiation.
Keywords: addition; phenothiazine; photochemistry; photoredox catalysis; redox potential